2016
DOI: 10.1111/ahg.12174
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs11643718SLC12A3and rs741301ELMO1Variants with Diabetic Nephropathy in South Indian Population

Abstract: This study reports on the association of genetic variants selected from previous genome-wide association studies for type 2 diabetic nephropathy in south Indians. Eight variants were genotyped in 601 type 2 diabetic subjects without nephropathy (DM) and 583 type 2 diabetic subjects with nephropathy (DN) by MassARRAY. The minor allele frequencies of rs11643718 SLC12A3 variant and rs741301 ELMO1 variant were significantly different between DM and DN groups (P = 0.029 and 0.016, respectively). A combined analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…The GWAS study has shown that the rs741301 polymorphism of the ELMO1 gene is a candidate diagnostic gene for DKD. We chose rs741301 polymorphism of ELMO1 gene as a candidate gene for DKD based upon findings from previous studies, but these prior studies are contradictory [12,[20][21][22][23][24][25][26][27][28][29]. To the best of our knowledge, none of the prior studies assessed the role of the ELMO1 gene with DKD among Polish patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GWAS study has shown that the rs741301 polymorphism of the ELMO1 gene is a candidate diagnostic gene for DKD. We chose rs741301 polymorphism of ELMO1 gene as a candidate gene for DKD based upon findings from previous studies, but these prior studies are contradictory [12,[20][21][22][23][24][25][26][27][28][29]. To the best of our knowledge, none of the prior studies assessed the role of the ELMO1 gene with DKD among Polish patients.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies confirmed the association of different SNP variants in the ELMO1 gene with susceptibility to DKD in patients from various populations: African Americans [20], European Americans [21], American Indians [22], Mexican Americans [23], Tunisian Arabs [24], as well as citizens of China [25], India [26][27], Iran [28], and Malaysia [29]. Unfortunately, it is impossible to draw a unified conclusion from the outcomes because these studies were different in terms of methodology and definition of DKD.…”
Section: Snp Genotypingmentioning
confidence: 95%
See 1 more Smart Citation
“…[ 11 , 12 ] In DM-DN, genetic susceptibility is mainly characterized by familial aggregation, and the prevalence of DN is different among different ethnic groups. [ 13 , 14 ] Recently, due to the development of genetic methods, multiple single nucleotide polymorphisms (SNPs) associated with DN susceptibility have been discovered, such as SLC12A3, [ 15 ] ACACβ, [ 16 ] AGTR1, [ 16 ] ELMO1, [ 17 , 18 ] MTHFR, [ 19 ] SLC12A3, [ 20 ] CNDP1, and CNDP2. [ 21 ] The matrix metallopeptidase-9 (MMP-9) gene is also one of the widely studied SNPs in DN.…”
Section: Introductionmentioning
confidence: 99%
“…In a genome-wide case control association study, Shimazaki et al found that a single nucleotide polymorphism in the 18th intron of the ELMO1 gene is strongly associated with diabetic nephropathy in Japanese (3). Since then the association has been observed between the polymorphisms in the ELMO1 gene and diabetic nephropathy in Whites (4,5), Chinese (6), African Americans (7), Pima Indians (8), South Indians (9), and Iranians (10).…”
Section: Introductionmentioning
confidence: 99%